1991
DOI: 10.3109/00016349109007873
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin, somatostatin, insulin and gastrin concentrations vis‐à‐vis late pregnancy, breastfeeding and oral contraceptives

Abstract: Oxytocin concentrations increased during pregnancy and during medication with low-dose oral contraceptives (o.c.). Postprandial somatostatin concentrations were lower during medication with o.c. Insulin concentrations were elevated during pregnancy with the same tendency during medication with o.c. Gastrin levels were unaffected during the peripartal period and during medication with o.c. Women who were breastfeeders at 3 months after delivery had higher concentrations of oxytocin and lower somatostatin concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…This result is at odds with previous reports, where higher plasma oxytocin levels were observed for breastfeeding women compared to non-breastfeeding women (39, 40). It is important to note that only slightly more than 10% of the mothers had stopped breastfeeding at 2 months postpartum.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result is at odds with previous reports, where higher plasma oxytocin levels were observed for breastfeeding women compared to non-breastfeeding women (39, 40). It is important to note that only slightly more than 10% of the mothers had stopped breastfeeding at 2 months postpartum.…”
Section: Discussioncontrasting
confidence: 99%
“…In another study, levels of oxytocin were found to increase slowly until delivery and then decrease up to 8 weeks postpartum (13). One group reported higher levels of oxytocin at 36 weeks of pregnancy than 1 day after delivery or later (14). Another group observed a steady increase in plasma levels of the oxytocin precursor, neurophysin–oxytocin, during pregnancy followed by a decrease between 7 and 42 days postpartum but stable plasma oxytocin levels during pregnancy (15).…”
Section: Introductionmentioning
confidence: 99%
“…When we treated the constipated women with intranasal oxytocin, less abdominal pain and discomfort was seen among those who also suffered from IBS (2). In the present trial, which is the only one examining abdominal pain during pregnancy and breast feeding in healthy women, there was a trend towards more abdominal pain during late pregnancy, when the oxytocin levels are at the highest levels (8). Other hormonal changes, such as sexual hormones and insulin, occurring at the same time may counteract the effects of oxytocin (8).…”
Section: To the Editor;mentioning
confidence: 44%
“…In the present trial, which is the only one examining abdominal pain during pregnancy and breast feeding in healthy women, there was a trend towards more abdominal pain during late pregnancy, when the oxytocin levels are at the highest levels (8). Other hormonal changes, such as sexual hormones and insulin, occurring at the same time may counteract the effects of oxytocin (8). Further, the abdominal pain during pregnancy may have a different etiology than abdominal pain in IBS.…”
Section: To the Editor;mentioning
confidence: 59%
“…There is also evidence to suggest that circulating oxytocin levels during pregnancy predict breastfeeding duration (Silber et al, 1991). The mechanisms through which these relationships occur are not clear, but it may be that this early OT exposure primes the milk ejection…”
Section: Accepted Manuscriptmentioning
confidence: 98%